Teacher–student relationship, task persistence, early academic skills and motivation at preschool - Jaruševičiūtė, Vilija (2019)
The main aim of the current thesis was to examine whether task persistence can act as a mediator in the association between teacher–student relationship and early academic skills and motivation. The present thesis concentrated on preschool students (around six years old) and their teachers who are important figures during the transitional period from the kindergarten to the first grade. Therefore, this thesis suggested one of the possible mechanisms of how teacher–student relationship relates to early academic skills and motivation of preschool students. For the purposes of the current thesis, quantitative concurrent data from the study Get involved! (Lithuania) was used. Teacher–student relationship and task persistence of preschool students were measured by teacher questionnaires, students had individual tests for early academic skills, and motivation of students was assessed by interviews. Results of the study confirmed the positive connections between close teacher–student relationship and early academic skills and motivation via the task persistence of preschool students. The closer relationship with students teachers perceived, the better task persistence and academic outcomes students had. In contrast, the more conflicting teacher–student relationship was, the lower the task persistence and, in turn, the lower early academic skills and motivation of preschoolers were. The current thesis presented one of the tools of how teachers can promote early academic skills and motivation among preschoolers. Close teacher–student relationship should be encouraged because it relates to higher task persistence and, in turn, promotes early academic skills and motivation of students.